Pelatihan Perancangan dalam Melaksanakan Penilaian Proses dan Hasil Belajar bagi Guru Taman Kanak-Kanak di Kota Bandar Lampung - Nopiana Nopiana; Ari Sofia; Nia Fatmawati (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2026)
Assessment is a crucial component of early childhood education (PAUD) learning because it serves to monitor children's development and learning outcomes holistically. However, many kindergarten (TK) teachers still experience difficulties in designing and implementing assessments of the learning process and outcomes according to the characteristics of early childhood. This community service activity aims to improve the competence of kindergarten teachers in Bandar Lampung City in designing and implementing assessments of the learning process and outcomes through structured training. The implementation methods include lectures, discussions, workshops, practical assessment instrument development, and mentoring. The subjects of the activity were kindergarten teachers from several kindergarten institutions in Bandar Lampung City. The results of the activity showed an increase in teachers' understanding of the PAUD assessment concept, as well as an increase in teachers' ability to develop assessment instruments for the learning process and outcomes that are in accordance with the principles of authentic assessment. This training has a positive impact on teachers' professional competence and the quality of assessment implementation in kindergarten institutions.